Transgenic mice overexpressing human ALOX15 under the control of the aP2 promoter are partly protected in the complete Freund’s adjuvant-induced paw inflammation model - Dagmar Heydeck; Kumar R. Kakularam; Dominika Labuz; Halina Machelska; Nadine Rohwer; Karsten Weylandt; Hartmut Kuhn (Inflammation Research, 2023)
Background, objectives and design Arachidonic acid 15-lipoxygenase (ALOX15) has been implicated in the pathogenesis of inflammatory diseases but since pro- and anti-inflammatory roles have been suggested, the precise function of this enzyme is still a matter of discussion. To contribute to this discussion, we created transgenic mice, which express human ALOX15 under the control of the activating protein 2 promoter (aP2- ALOX15 mice) and compared the sensitivity of these gain-of-function animals in two independent mouse inflammation models with Alox15-deficient mice (loss-of-function animals) and wildtype control animals. Materials and methods Transgenic aP2- ALOX15 mice were tested in comparison with Alox15 knockout mice (Alox15 −/− ) and corresponding wildtype control animals (C57BL/6J) in the complete Freund’s adjuvant induced hind-paw edema model and in the dextran sulfate sodium induced colitis (DSS-colitis) model. In the paw edema model, the degree of paw swelling and the sensitivity of the inflamed hind-paw for mechanic (von Frey test) and thermal (Hargreaves test) stimulation were quantified as clinical readout parameters. In the dextran sodium sulfate induced colitis model the loss of body weight, the colon lengths and the disease activity index were determined. Results In the hind-paw edema model, systemic inactivation of the endogenous Alox15 gene intensified the inflammatory symptoms, whereas overexpression of human ALOX15 reduced the degree of hind-paw inflammation. These data suggest anti-inflammatory roles for endogenous and transgenic ALOX15 in this particular inflammation model. As mechanistic reason for the protective effect downregulation of the pro-inflammatory ALOX5 pathways was suggested. However, in the dextran sodium sulfate colitis model, in which systemic inactivation of the Alox15 gene protected female mice from DSS-induced colitis, transgenic overexpression of human ALOX15 did hardly impact the intensity of the inflammatory symptoms. Conclusion The biological role of ALOX15 in the pathogenesis of inflammation is variable and depends on the kind of the animal inflammation model.

The progesterone derivative dydrogesterone down-regulates neurokinin 1 receptor expression on lymphocytes, induces a Th2 skew and exerts hypoalgesic effects in mice - Arif Suphi Orsal; Sandra Blois; Dominika Labuz; Eva M. J. Peters; Martin Schaefer; Petra C. Arck (Journal of Molecular Medicine, 2006)